2006
DOI: 10.1111/j.1574-6941.1997.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection by temperature of nitrate-reducing bacteria from estuarine sediments: species composition and competition for nitrate

Abstract: Nitrate‐metabolising bacteria were isolated from estuarine sediment in carbon‐limited anaerobic chemostats with nitrate as the only electron acceptor, at constant low temperature (5°C), constant high temperature (20°C), or square wave temperature cycle (5–20°C over 24 h). The steady‐state communities isolated were sampled randomly, and isolates identified. At constant 20°C and under cycling temperature the communities were dominated by bacteria with obligately fermentative metabolism; Klebsiella spp. at 20°C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 41 publications
3
31
1
1
Order By: Relevance
“…Nevertheless, a reasonable exponential fit for 3 -4 points could be obtained for the cell numbers, suggesting that most of the assemblage underwent exponential growth in the bags. The generation times computed for the incubations are longer than usually observed under culture conditions (on the order of 5 -45 hr; Otte et al 1996;Ogilvie et al 1997), but the curve fits implied that growth commenced almost immediately in some incubations (e.g., ETSP and AS Station 17).…”
Section: Denitrification Ratesmentioning
confidence: 96%
“…Nevertheless, a reasonable exponential fit for 3 -4 points could be obtained for the cell numbers, suggesting that most of the assemblage underwent exponential growth in the bags. The generation times computed for the incubations are longer than usually observed under culture conditions (on the order of 5 -45 hr; Otte et al 1996;Ogilvie et al 1997), but the curve fits implied that growth commenced almost immediately in some incubations (e.g., ETSP and AS Station 17).…”
Section: Denitrification Ratesmentioning
confidence: 96%
“…Although there is no data specifically on tropical isolates, previous work in temperate European estuarine sediments (King and Nedwell 1984;Jørgensen 1989) have shown that nitrate ammonifiers predominate over denitrifiers during higher temperature summer periods, but denitrifiers predominate during autumn and winter. Furthermore, in anaerobic chemostat isolations from temperate sediments Ogilvie et al (1997) showed that only nitrate ammonifiers (Klebsiella and Enterobacter) were isolated from estuarine sediment in anaerobic chemostats at 20uC, but only denitrifiers at low temperature, and the reason seemed to be the greater affinity for nitrate (as measured by a A ) of nitrate ammonifiers than denitrifiers for nitrate at higher temperatures. If these bacteria are representative of a general metabolic trend, it would suggest that at tropical temperatures permanently .…”
Section: Discussionmentioning
confidence: 99%
“…The estuary catchment is 500 km 2 , of which the River Colne drains 300 km 2 , much of which is rich, arable land. The estuary exhibits strong gradients of both NO and Ϫ 3 NH concentrations decreasing with distance downstream ϩ 4 (King and Nedwell 1987;Ogilvie et al 1997a;Robinson et al 1998) as a result of inputs from the River Colne and a major sewage treatment work at Colchester . Three benthic sampling sites were selected ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…et al 2000b). This is subject to influences of various factors that affect rates of denitrification and the bacterial community of denitrifiers in sediments (King and Nedwell 1987;Ogilvie et al 1997b;Dong et al 2000b), of which nitrate concentration in the water column and freshwater flushing time of an estuary seem to be dominating factors. Although the main end product of denitrification is in the form of N 2 , nitrous oxide is also produced in the process of denitrification either as intermediate or as an end product or as both (Lloyd 2000;.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation